Transformation of expectations of integrated reporting audit results of users - K.P. Melnyk (Економіка, управління та адміністрування)
One of the prerequisites for using an integrated report is to obtain a sufficient level of confidence in it, in particular, based on the audit report. In this regard, the expectations of users of the audit results are broadened by including additional quantitative and qualitative parameters that are taken into account when information evaluation criteria are formulating. Thus, there is a need to clarify the approach to identifying and assessing users' expectations about results of the data audit contained in the integrated reporting of entities, which affected on the purpose of the study. It is determined that the interest of the users of information disclosed in integrated reporting may affect the nature of interest in the results of its audit. The classification of the expectations of the users of the results on the basis of their formalization and the consequences of the integrated reporting audit are substantiated. It is established that the meaningful characteristics of the expectations of the audit results of the users are determined by the presence of the audit report, the identification of its purpose, the individual parameters of the presented information, the compliance of the reporting data with predefined criteria and the availability of information regarding additional circumstances. The findings of the study allow to solve a number of problems related to the identification and detail of the audit objectives of the integrated reporting, the clarification of its subject area, and, as a consequence, the improvement of measures aimed at achieving the audit objective as an assurance task. Among the areas for further research, it is proposed to identify the development of methodological approaches to improve the integrated reporting audit activities based on the recognition of the priority of users' expectations of its results.